Clinical Characteristics, Prognostic Risk Factors, and Primary Treatment for Elderly Patients with Primary Central Nervous System Lymphoma: A Seer Database-Based Research - Zhang M; Yang R; Du Y; Feng H; Liu Y; Liu H; Wu D; Niu F; He P (Blood and Lymphatic Cancer: Targets and Therapy)
Mengyao Zhang,* Runyu Yang,* Yue Du,* Hui Feng, Yi Liu, Haibo Liu, Di Wu, Fan Niu, Pengcheng He Department of Hematology, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, China, Xi’an, Shaanxi, 710061, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fan Niu, Department of Hematology, First Affiliated Hospital of Xi’an Jiaotong University, No. 277 Yanta West Road, Xi’an, Shaanxi, 710061, People’s Republic of China, Email niufan@xjtufh.edu.cn Pengcheng He, Department of Hematology, First Affiliated Hospital of Xi’an Jiaotong University, No. 277 Yanta West Road, Xi’an, Shaanxi, 710061, People’s Republic of China, Email hepengcheng@xjtu.edu.cnBackground: Primary central nervous system lymphoma (PCNSL) is a highly aggressive extranodal non-Hodgkin’s lymphoma. Moreover, there is currently no specific prognostic model for elderly PCNSL patients.Methods: This study retrospectively selected patients diagnosed with PCNSL between 1975 and 2016 from the National Cancer Institute Surveillance, Epidemiology, and End Results Database (SEER NCI). The COX model was used to determine the risk factors for overall survival (OS) and disease-specific survival (DSS). The prognostic prediction models for DSS and OS were developed by integrating significant covariates identified through multivariate analysis.Results: A total of 3,554 patients with PCNSL were included in this retrospective study based on inclusion and exclusion criteria. Significant differences exist in clinical profiles between elderly (≥ 60 years) and younger (< 60 years) patients with PCNSL. The results showed that the age at diagnosis, pathological subtype, whether or not they have undergone surgical treatment, and whether or not they have received chemotherapy are independent risk factors for DSS, among elderly PCNSL patients. In addition to the risk factors, etc for DSS, human immunodeficiency virus (HIV) infection was also an independent risk factor for OS. Based on this, we developed nomograms to estimate OS and DSS for 1, 2, and 3 years.Conclusion: This study found differences in baseline data between elderly PCNSL patients and younger PCNSL patients. Surgery and chemotherapy are associated with better OS and DSS. However, in the long run, radiotherapy is not beneficial to OS and DSS of elderly PCNSL patients.Keywords: primary central nervous system lymphoma, elderly patients, prognostic risk factors, SEER database, primary treatment